Improving hypertension surveillance from a data management prospective: Data requirements for implementation of population-based registry - Mostafa Shanbehzadeh; Hadi Kazemi-Arpanahi; Arezo Arzani-Birgani; Azimeh Karimyan; Fatemeh Mobasheri (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Hypertension (HTN) has become a major public health problem which can cause serious complications when it is not well-controlled. Prevention and effective care of HTN require a population-based registry. Thus, establishing this registry can be used to collect comprehensive, timely, and reliable data on epidemiology cases. The aim is to create a registry for the collection of highly required prospective data that will present an in-depth analysis of the characteristics of all individuals with HTN and track them over a particular chronological interval. MATERIALS AND METHODS: The study was divided into three phases: At first, a comprehensive literature review was conducted to determine the proposed data classes and data fields. Then, the final minimum data set was designed by a two-round Delphi consensus approach of 20 experts of cardiologists, nephrologists, nutritionist, and health information management. Finally, a web-based registry system was developed by a Structured Query Language environment. RESULTS: A total of two clinical and nonclinical data categories with nine data classes and 68 data fields were selected for their inclusion in the registry following the consensus phase. A web-based registry was designed with a modular and layered architecture. CONCLUSIONS: This study provides an appropriate information infrastructure for active tracing and monitoring of individuals with HTN. It has provided a practical information system allowing quality improvement, aggregate reporting for planning, and research purposes.